Kontrasepsi dan Jawaban Gereja dalam Membangun Keluarga Kristiani dari Casti Connubi sampai Amoris Laetitia - Suwito, Benny (Lux et Sal, 2022)
As a follower of Christ, the life of Christians must reflect on their daily reality. However, it is not always easy to achieve. Often, Christian families live in an environment that does not support them living their faith. Contraception and contraceptive mentality are flourished robustly in the society. In such situations, the Church gives directions to the faithful through its official teachings. Everything is returned to the divine plan that Christ has revealed to the Church. Documents from Casti Connubi to Amoris Laetitia show this thing.